Creme brulee I / Saidah Ismail ... [et al.] - Ismail, Saidah; Md Isa, Haslinda; Md Said, Mohd Saupi; Che Mustafa, Norliza; Idris, Norhayati (UiTM Press, 2021)
This book is specifically written for students who will be taking French as a third language at Universiti Teknologi MARA. Creme Brulee I provide the basis for learning the French language. It is an introduction to the French language and suitable for beginners. It was written to meet the needs of 28 teaching hours in one semester. This book contains four basic topics which are Bienvenue, Ma Famille, A I'Universite, and Mon Pays. Each topic consists of a dialogue, followed by notes on vocabulary, grammar, culture and proverbs. Exercises and samples of test questions are also included to reinforce students' understanding.